Epigallocatechin Gallate Effectively Affects Senescence and Anti-SASP via SIRT3 in 3T3-L1 Preadipocytes in Comparison with Other Bioactive Substances. (23rd October 2020) - Lilja, Stephanie; Oldenburg, Julia; Pointner, Angelika; Dewald, Laura; Lerch, Mariam; Hippe, Berit; Switzeny, Olivier; Haslberger, Alexander
Abstract : Aim . We investigated different bioactive compounds including epigallocatechin gallate (EGCG), anthocyanidin, resveratrol, phloretin, spermidine, butyrate, and β -hydroxybutyrate with regard to their effect on SIRT3 via NRF2 and modulation of the proinflammatory senescence-associated secretory phenotype (SASP) in senescence induced 3T3-L1 preadipocytes. Methods . For induction of senescence, 3T3-L1 preadipocytes were incubated with bromodeoxyuridine (BrdU) for 8 days. Cell cycle inhibition was observed, and β -galactosidase activity was measured. After BrdU treatment, cells were treated with different bioactive compounds in various concentrations for 96 h. ELISA was used for determining proinflammatory cytokine IL6 in SASP cells. Results . CDKN1a increased significantly after BrdU incubation compared to untreated control (p < 0.01 ). All secondary plant ingredients used for treatment, but not anthocyanidin 50  μ M, decrease CDKN1a expression (p < 0.05 ), whereas most endogenous substances did not attenuate CDKN1a . IL6 secretion positively correlated with CDKN1a (p < 0.01 ), whereas EGCG could diminish both, IL6 and CDKN1a with the strongest effect (p < 0.01 ). Although NRF2 positively correlated with SIRT3 activation (p < 0.05 ), only resveratrol (p < 0.01 ) and anthocyanidin (p < 0.05 ) could activate NRF2 significantly. Solely anthocyanidin 50  μ M (p < 0.05 ) and 100  μ M (p < 0.01 ) and EGCG 50  μ M (p < 0.01 ) could increase SIRT3 expression. Activation of SIRT3 with EGCG correlated with lowered IL6 secretion significantly (p < 0.05 ) but not with anthocyanidin. Conclusion . Accumulation of senescent cells in adipose tissue plays an important role in obesity and age-related diseases. SIRT3, located in the mitochondria, can regulate ROS via different pathways. Thus, targeting SIRT3 activating compounds such as EGCG may delay senescence of cells and senescence induced inflammatory processes.